Social policy review 15 UK and international perspectives - Bochel, Catherine ca. 20./21. Jh; Ellison, Nicholas 1952-; Powell, Martin 1961- (The Policy Press, 2003)
Social Policy Review 15 continues the tradition of providing a different style and approach to policy issues from that found in most academic journals and books. This volume combines issues such as globalization, Europe and pensions with an examination of the current and historical contexts of social policy